1996
DOI: 10.1103/physrevb.53.9688
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of the charged boson fluid atT=0

Abstract: The diffusion Monte Carlo ͑DMC͒ method is used to analyze various properties of the three-dimensional plasma of charged bosons in the homogeneous fluid regime, over the density range 1рr s р160 extending from the so-called uniform limit (r s Ͻ1) to the crystalline phase (r s Ͼ160). The data on the static density response function (k) extend to intermediate and high wave number k the work of Sugiyama, Bowen, and Alder ͓Phys. Rev. B 46, 13 042 ͑1992͔͒ and allow us to extract the static local-field factor G(k) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 29 publications
4
44
0
Order By: Relevance
“…for n 0 /n close to unity, in line of principle). This statement is quantitatively tested in Table I, where we compare our results for n 0 /n at T = 0 with the DMC data of Moroni et al 25 over the whole fluid range up to Wigner crystallization. It is clear from Table I that, rather surprisingly, the Bogoliubov approach is almost fully quantitative up to r s ≃ 5, i.e.…”
Section: The Three-dimensional Charged-boson Fluidmentioning
confidence: 85%
See 4 more Smart Citations
“…for n 0 /n close to unity, in line of principle). This statement is quantitatively tested in Table I, where we compare our results for n 0 /n at T = 0 with the DMC data of Moroni et al 25 over the whole fluid range up to Wigner crystallization. It is clear from Table I that, rather surprisingly, the Bogoliubov approach is almost fully quantitative up to r s ≃ 5, i.e.…”
Section: The Three-dimensional Charged-boson Fluidmentioning
confidence: 85%
“…By comparison of results on the 3D fluid with diffusion Monte Carlo data 25 we have found that the Bogoliubov approach may yield quantitatively useful predictions over a surprisingly wide range of coupling strengths and of deviations of the condensate fraction from unity. At finite temperature the behaviour of the charged 2D gas is qualitatively wholly similar to that of its better known neutral analogue: well below the Kosterlitz-Thouless transition a slow power-law decay is seen in the one-body density matrix, heralding extended-range correlations in phase fluctuations and the formation of a condensate over regions of finite size.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations